Quantification of all-trans retinoic acid by liquid chromatography-tandem mass spectrometry and association with lipid profile in patients with Type 2 diabetes - Morgenstern, Jakob; Fleming, Thomas; Kliemank, Elisabeth; Brune, Maik; Nawroth, Peter Paul; Fischer, Andreas (Metabolites, 2021)
Retinoic acids are vitamin A metabolites that have numerous essential functions in humans, and are also used as drugs to treat acne and acute promyelocytic leukemia. All-trans retinoic acid (atRA) is the major occurring metabolite of retinoic acid in humans. This study provides a sensitive and specific liquid chromatography–tandem mass spectrometry approach in order to quantify atRA in human plasma samples. The isolation of atRA by hyperacidified liquid–liquid extraction using hexane and ethyl acetate resulted in a recovery of 89.7 ± 9.2%. The lower limit of detection was 20 pg·mL−1, and 7 point calibration displayed good linearity (R2 = 0.994) in the range of 50–3200 pg mL−1. Selectivity was guaranteed by the use of two individual mass transitions (qualifier and quantifier), and precision and accuracy were determined intraday and interday with a coefficient variation of 9.3% (intraday) and 14.0% (interday). Moreover, the method could be used to isolate atRA from hyperlipidemic samples. Applying this method to plasma samples from patients with poorly controlled Type 2 diabetes significantly decreased atRA plasma levels as compared to those of the healthy controls. In addition, atRA concentrations were highly associated with increased low-density lipoprotein (LDL) and decreased high-density lipoprotein (HDL) cholesterol levels.